BS EN 3311. Aerospace series. Titanium alloy TI-P64001 (Ti-6Al-4V). Annealed. Bars for machining. D < 300 mm. 900 MPa ≤ Rm ≤ 1 160 MPa. (21st July 2021) - British Standards Institution
No abstract available